2011
DOI: 10.2214/ajr.10.5733
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Uncommon Fractures on Skeletal Surveys Performed to Evaluate for Suspected Abuse in 930 Children: Should Practice Guidelines Change?

Abstract: In skeletal surveys performed for suspected child abuse, fractures limited to sites other than the long bones, ribs, skull, and clavicles are rare. The additional radiation exposure and cost of obtaining radiographs of the spine, pelvis, hands, and feet may outweigh their potential benefit. Given the rarity of fractures of the spine, pelvis, hands, and feet, consideration may be given to eliminating those views from routine skeletal surveys performed to evaluate for suspected child abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 16 publications
6
44
0
2
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The small number of these fractures, and their frequent association with other evidence allowing the diagnosis of abuse, has triggered a suggestion that spine and pelvis views be omitted from SS1. 24,26 Others have opposed this viewpoint for spine fractures, 25,27,28 making the argument that there is high specificity for abuse when occult spine fractures are discovered, and that spine fractures, while uncommon, are not rare. The low initial prevalence of spine and pelvis fractures on both SS1 and SS2 supports decreasing repeated exposure by eliminating these views from SS2.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The small number of these fractures, and their frequent association with other evidence allowing the diagnosis of abuse, has triggered a suggestion that spine and pelvis views be omitted from SS1. 24,26 Others have opposed this viewpoint for spine fractures, 25,27,28 making the argument that there is high specificity for abuse when occult spine fractures are discovered, and that spine fractures, while uncommon, are not rare. The low initial prevalence of spine and pelvis fractures on both SS1 and SS2 supports decreasing repeated exposure by eliminating these views from SS2.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study reported that SSs revealed additional fractures in 13% (124 of 930) of children ,2 years old evaluated for suspected abuse. 11 Even higher incidences (25%-30%) of occult fractures have been reported in studies of children ,2 years old diagnosed with physical abuse. 12,13 Given the substantial likelihood of occult fractures in young victims of physical abuse, the American Academy of Pediatrics recommends performing SS in all cases of suspected physical abuse in children ,2 years old, but not in cases in which abuse and occult fractures are unlikely.…”
Section: What This Study Addsmentioning
confidence: 96%
“…This supplemental review identified 18 relevant articles from which data were abstracted and summarized for the expert panel. [10][11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36] …”
Section: Literature Reviewmentioning
confidence: 99%
“…SSs reveal fractures that are not clinically suspected on the basis of history or physical examination in 10% to 40% of children ,2 years old evaluated for suspected abuse. [1][2][3][4][5][6] In addition to identifying fractures requiring medical treatment, SSs can document fractures and other findings that do not require medical treatment but are important to safeguard the well-being of the child. Specific patterns of fractures can confirm a diagnosis of abuse and allow for protection of the child.…”
Section: What This Study Addsmentioning
confidence: 99%